Morphometric evaluation of the anterior cranial fossa during the prenatal stage in humans and its clinical implications. - Wojciech Derkowski; Alicja Kędzia; Krzysztof Dudek; Michał Glonek (PLoS ONE)
The study examines the morphometric development of the anterior cranial fossa in human fetuses and its clinical implications. The anterior cranial fossa, crucial for protecting the frontal lobes, was analyzed during prenatal development using innovative computer image processing techniques. We hypothesized that the growth of the anterior cranial fossa is not uniform throughout fetal development and that changing geometric relationships are important for possible therapeutic interventions in cases of congenital defects. A metrological assessment was conducted on 77 fetuses, aged 10 to 27 weeks of gestation, to investigate developmental patterns, including symmetry, sexual dimorphism, and structural changes relative to other cranial fossae. Key findings revealed a decrease in the anterior cranial fossa angle, compensated by an increase in the middle cranial fossa angle. Symmetry in cranial base development was observed, and sexual dimorphism was evident, with male fetuses showing larger angles and females displaying greater height of the crista galli. These results were discussed in the context of existing anatomical and imaging studies. Clinically, the findings provide insights into the pathomechanism of congenital skull and brain defects, supporting the potential for early diagnostic and therapeutic interventions. Our study leads to the conclusion that the growth of the anterior cranial fossa is not uniform; in the first trimester, allometric growth occurs, while at the same time the angle of the anterior cranial fossa decreases and its depth increases towards the middle cranial fossa. In the second trimester, growth continues but becomes more uniform, with only minor changes in the angle of the anterior cranial fossa. There is a gradual decrease in the angle between the smaller wings of the sphenoid bone as the depth of the anterior cranial fossa increases in the frontal plane. Sexual dimorphism is visible in the area of ​​the anterior cranial fossa already in the prenatal period.